Osborne, Pam (London, 2011)
2011 "Osborne, Pam", 2011, HistoryTalk Pam completed a course in commercial training at school, after which she did clerical work in various companies mainly in their sales departments, including British Eagle Airways (based at Heathrow), Minimax, and Norsk Hydro UK Ltd. After raising a family she returned to work on a part-time basis, running a pre-school with the assistance of other mothers., and then worked in education as a PA at Brunel University.